1998
DOI: 10.1016/s1074-7613(00)80581-6
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Generation of Lymphohematopoietic Cells from Endothelial Cells Purified from Murine Embryos

Abstract: We have investigated the lymphohematopoietic potentials of endothelial cells (EC) and hematopoietic cells (HPC) sorted from embryos. Expression of VE-cadherin, CD45, and Ter119 was used to distinguish EC (VE-cadherin+CD45-Ter119-) from HPC (VE-cadherin-CD45+). Thus defined, EC population takes up acetylated LDL and coexpresses CD31, Flk1, and CD34. In E9.5 embryos, EC from yolk sac (YS) and the embryo proper generate blood cells, including lymphocytes. Thus, lymphohematopoietic EC do exist in the embryo, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
301
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 337 publications
(318 citation statements)
references
References 28 publications
17
301
0
Order By: Relevance
“…However, based on expression of the transcription factor Runx1 (discussed below) only a subset of the endothelium in these sites is believed to be hemogenic [36]. Functionally, hemogenic endothelium has been defined as displaying an endothelial phenotype and morphology and having the capacity to form hematopoietic offspring and endothelial tubules/sheets in culture [37,38]. The overlap in cell surface marker expression on (hemogenic) endothelial and hematopoietic cells has further confounded the identification and isolation of hemogenic endothelium.…”
Section: Identification Of Hemogenic Endotheliummentioning
confidence: 99%
See 1 more Smart Citation
“…However, based on expression of the transcription factor Runx1 (discussed below) only a subset of the endothelium in these sites is believed to be hemogenic [36]. Functionally, hemogenic endothelium has been defined as displaying an endothelial phenotype and morphology and having the capacity to form hematopoietic offspring and endothelial tubules/sheets in culture [37,38]. The overlap in cell surface marker expression on (hemogenic) endothelial and hematopoietic cells has further confounded the identification and isolation of hemogenic endothelium.…”
Section: Identification Of Hemogenic Endotheliummentioning
confidence: 99%
“…Combination of VECadh or CD31 with the hematopoietic markers CD41 [40][41][42][43], CD45 [44] and Ter119 [45] has been used to separate endothelial from hematopoietic cells (e.g. [38,[46][47][48]), and other identification strategies have also been employed e.g. [49] [50].…”
Section: Identification Of Hemogenic Endotheliummentioning
confidence: 99%
“…Intraembryonic HSCs were noted to arise on the luminal aspect of endothelial cells in the dorsal aorta and vitelline artery. Diverse lineagemarking experiments based on metabolic labeling of endothelium in avian embryos in ovo (Jaffredo et al 1998), purification of mouse embryonic endothelium by flow cytometry (Nishikawa et al 1998), or tagging of angio-hematopoietic cells in transgenic mice (North et al 2002) have all suggested the conclusion that discrete subsets of vascular endothelial cells transiently exhibit blood-forming potential during vertebrate development, as originally suggested by Sabin (1920).…”
Section: Introductionmentioning
confidence: 92%
“…It should be kept in mind that hematopoiesis from vessel walls was likely an ancestral mechanism of blood cell generation in evolution, inasmuch as, in addition to converging studies in bird and mouse embryos (Jaffredo et al 1998, Nishikawa et al 1998, North et al 2002, Bollerot et al 2005, similar hematogenous embryonic aortic cells have been characterized in amphibian and fish embryos (Ciau-Uitz et al 2000, Gering andPatient, 2005). Important genetic analyses performed in the same lower vertebrates have confirmed that molecular signaling through Hedgehog, Notch, and VEGF is essential to the development of both adult hematopoietic cells and the dorsal aorta, further associating the emergence of HSCs with the aortic blood-forming endothelium (Brown et al 2000, Gering andPatient, 2005).…”
Section: Hemogenic Endothelium In the Human Embryo And Fetusmentioning
confidence: 99%
See 1 more Smart Citation